Calcitonin gene-related peptide and pain: a systematic review - Schou, Wendy Sophie; Ashina, Sait; Amin, Faisal Mohammad; Goadsby, Peter J.; Ashina, Messoud (Journal of headache and pain, 2017)
Background Calcitonin gene-related peptide (CGRP) is widely distributed in nociceptive pathways in human peripheral and central nervous system and its receptors are also expressed in pain pathways. CGRP is involved in migraine pathophysiology but its role in non-headache pain has not been clarified. Methods We performed a systematic literature search on PubMed, Embase and ClinicalTrials.gov for articles on CGRP and non-headache pain covering human studies including experimental studies and randomized clinical trials. Results The literature search identified 375 citations of which 50 contained relevant original data. An association between measured CGRP levels and somatic, visceral, neuropathic and inflammatory pain was found. In 13 out of 20 studies in somatic pain conditions, CGRP levels had a positive correlation with pain. Increased CGRP levels were reported in plasma, synovial and cerebrospinal fluid in subjects with musculoskeletal pain. A randomized clinical trial on monoclonal antibody, which selectively binds to and inhibits the activity of CGRP (galcanezumab) in patients with osteoarthritis knee pain, failed to demonstrate improvement of pain compared with placebo. No studies to date have investigated the efficacy of monoclonal antibodies against CGRP receptor in non-headache pain conditions. Conclusion The present review revealed the association between measured CGRP levels and somatic, visceral, neuropathic and inflammatory pain. These data suggest that CGRP may act as a neuromodulator in non-headache pain conditions. However, more studies are needed to fully understand the role of CGRP in nociceptive processing and therapy of chronic pain.